1990
DOI: 10.1159/000243297
|View full text |Cite
|
Sign up to set email alerts
|

Human Neonatal Hypocalcemia

Abstract: Hypocalcemia is commonly observed in the neonatal period and is usually transient from a few days to a few weeks. On only rare occasions is neonatal hypocalcemia permanent and secondary to congenital hypoparathyroidism caused by either isolated absence of parathyroid glands or in association with other malformations. Most cases of neonatal hypocalcemia fall into one of two clinical categories. Namely early neonatal hypocalcemia occurs in 24–48 h of life and it is usually observed in premature infants or infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 13 publications
(20 reference statements)
1
10
0
Order By: Relevance
“…This is an important cause of neonatal seizures. 16,17 Also, the role of hypoxic- 18,19 In the present study, the laboratory findings between babies who survived and those who died from perinatal asphyxia revealed significantly mean haematocrit, plasma potassium and urea were significantly higher among babies who died than those who survived asphyxia in the first 24 hours of life while plasma sodium wan glucose were significantly lower. Basu et al in India also found mean serum sodium level was significantly lower; mean serum potassium was higher than controls.…”
supporting
confidence: 46%
“…This is an important cause of neonatal seizures. 16,17 Also, the role of hypoxic- 18,19 In the present study, the laboratory findings between babies who survived and those who died from perinatal asphyxia revealed significantly mean haematocrit, plasma potassium and urea were significantly higher among babies who died than those who survived asphyxia in the first 24 hours of life while plasma sodium wan glucose were significantly lower. Basu et al in India also found mean serum sodium level was significantly lower; mean serum potassium was higher than controls.…”
supporting
confidence: 46%
“…Approximately half of the infants of pre-existing diabetic and gestational diabetic women develop early transient hypocalcemia. 15,16 Often, hypocalcemic infants display low serum magnesium values. 3 Although the cause for the high incidence of this complication is unclear, it is well recognized that it relates to the severity of maternal diabetes, and perinatal distress.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal hypocalcaemia is the most important and at the same time most commonly occuring postnatal disturbance of calcium metabolism [5,19]. The pathogenesis is complex and not yet fully understood and in most cases neonatal hypocalcaemia remains clinically inapparent.…”
Section: Discussionmentioning
confidence: 99%